Rhetorical Adaptation in the Greek Historians, Josephus, and Acts vol II : Embedded Speeches, Audience Responses, and Authorial Persuasion - Duncan, John M., (Biblical Interpretation Series ;, 2023)
Greco-Roman rhetorical theorists insist that speakers must adapt their speeches to their audiences in order to maximize persuasiveness and minimize alienation. Ancient historians adorn their narratives with accounts of attempts at such rhetorical adaptation, the outcomes of which decisively impact the subsequent course of events. These depictions of speaker-audience interactions, moreover, convey crucial didactic/persuasive insights to the historians' own audiences. This monograph presents a detailed comparative analysis of the intra- and extra-textual functions of speeches and audience responses in Greek historiography, Josephus, and Acts, with special emphasis on Luke's distinctive depiction of the apostles as adaptable yet frequently alienating orators. This is volume II of a set of two volumes.